Teach for attention! a tool belt of strategies for engaging students with attention challenges - Werb, Ezra (Free Spirit Publishing Inc., 2019)
"Book for educators about teaching students with ADHD and other attention challenges. Includes teaching strategies for students with ADHD, low self-confidence, distraction, and other attention challenges. Dozens of true classroom stories that show the strategies in action. Helps teachers make simple fixes without changing their approach or revamping their curriculum"--Provided by publisher.